2021
DOI: 10.1101/2021.04.17.440084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phytophthora capsici sterol reductase PcDHCR7 has a role in mycelium development and pathogenicity

Abstract: The de novo biosynthesis of sterols is critical for eukaryotes, however, some organisms lack this pathway including most oomycetes. Phytophthora spp. are sterol auxotroph but remarkably, have retained a few genes encoding enzymes in the sterol biosynthesis pathway. Here we investigated the function of PcDHCR7, a gene in Phytophthora capsici predicted to encode the Δ7-sterol reductase. When expressed in Saccharomyces cerevisiae, PcDHCR7 showed a Δ7-sterol reductase activity. Knocking out PcDHCR7 in P. capsici r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…For example, PAU : PleasenotethatasperPLOSstyle; iftwodifferentspeciessharethesamegenus hytophthora cactorum seems to have a preference for taking up Δ 5 sterols over Δ 5,7 sterols and tends to transform Δ 5,7 sterols into Δ 5 ones [21], probably mediated by DHCR7. This is corroborated by our recent study, which showed that DHCR7 in P. capsici is indeed responsible for reducing the double bond at that position [17]. When comparing different sterols or sterol mixtures, some stand out in showing higher activities than others.…”
Section: Can Oomycetes Survive Without Sterols?supporting
confidence: 83%
See 2 more Smart Citations
“…For example, PAU : PleasenotethatasperPLOSstyle; iftwodifferentspeciessharethesamegenus hytophthora cactorum seems to have a preference for taking up Δ 5 sterols over Δ 5,7 sterols and tends to transform Δ 5,7 sterols into Δ 5 ones [21], probably mediated by DHCR7. This is corroborated by our recent study, which showed that DHCR7 in P. capsici is indeed responsible for reducing the double bond at that position [17]. When comparing different sterols or sterol mixtures, some stand out in showing higher activities than others.…”
Section: Can Oomycetes Survive Without Sterols?supporting
confidence: 83%
“…For DHCR7 in Phytophthora capsici, we have evidence that this is indeed the case. It can indeed convert ergosterol into brassicasterol, and this modification seems to be essential for the completion of the asexual life cycle under certain conditions [17]. For producing zoospores in vitro, P. capsici requires medium supplemented with sterols.…”
Section: Cau : Pleaseconfirmthatallheadinglevelsarerepresentedcorrectlymentioning
confidence: 99%
See 1 more Smart Citation
“…cortex had genus selectivity and had a high antifungal effect on Rhizoctonia, Fusarium, Colletotrichum, and Botryosphaeria, but the antifungal effect on Phytophthora, Alternaria , and Botrytis was poor. We speculated that the reason for this difference may be the different contents of the cell wall or cell membrane structural components in different species, leading to the different difficulties of antifungal drugs entering the cells, for example, Phytophthora, most of which are ergosterol-deficient, so they are less sensitive to agents targeting cell membranes . Compared with other reported extracts of plants, the ethanol extract of M.…”
Section: Discussionmentioning
confidence: 99%
“…However, two enzymes (ERG3 and DHCR7) that function in the last steps of sterol biosynthesis were reported to present in Phytophthora and Pythium species (Wang et al, 2021a). These two enzymes were proposed to modify the exogenous sterols, especially DCHR7 was effective in converting ergosterol into brassicasterol in Phytophthora capsici (Wang et al, 2021b). Conversely, Saprolegnia parasitica and Aphanomyces euteiches are sterol autotrophs (i.e., synthesis cholesterol derivatives and fucosterol, respectively) and the sterol biosynthesis sub-branch has been identified in these two oomycete pathogens (Madoui et al, 2009;Warrilow et al, 2014).…”
Section: Introductionmentioning
confidence: 99%